Neonatal Scrub Typhus with an Eyelid Eschar Masquerading as "Late-onset Sepsis" - Dinesh Kumar Narayanasamy; Thirunavukkarasu Arun Babu (Wolters Kluwer Medknow Publications, 2022)
Background: Scrub typhus is a mite-borne infection caused by the bacterium, Orientia tsutsugamushi. It is re-emerging in many parts of South East Asia, particularly in rural India. Although no age group is immune to this infection, scrub typhus in neonates is rarely suspected and reported. Here, we report a neonate with scrub typhus who was initially misdiagnosed as "late-onset neonatal sepsis." Clinical Description: A 26-day-old exclusively breastfed infant presented with fever, vomiting, loose stools, abdominal distension, and refusal of feeds for 3 days. Examination revealed an irritable, febrile, and pale infant. She had tachycardia and facial puffiness. On abdominal examination, generalized distension with hepatosplenomegaly was noted. Blood investigations were suggestive of lymphocytic leukocytosis, thrombocytopenia, toxic granules in peripheral smear, and elevated C-reactive protein. Management: The infant was promptly started on empirical antibiotics for "late-onset sepsis." However, in view of poor response, other possible differential diagnoses were considered. Careful reexamination revealed a necrotic ulcer covered by a yellow scab with erythematous rim on the left lower eyelid. Based on the clinical presentation and an eschar-like lesion, scrub typhus was suspected. The neonate was started on oral azithromycin and immunoglobulin M (IgM) enzyme-linked immunosorbent assay (ELISA) testing for scrub typhus came back positive. Fever subsided immediately within 48 h and the infant was discharged after 7 days. Conclusion: Acute febrile illness due to scrub typhus can affect newborns. A high index of suspicion is required for early diagnosis. Timely treatment leads to prompt clinical response and reduced complications.